Modeling of the floating of non-metallic inclusions when pouring steel into a mold in top casting - Andriukhin, R. P.; Mamuzic, I.; Molchanov, L. S.; Synehin, Ye. V. (Сумський державний університет, 2020)
It is described in the paper the physical modeling of the metal flows pattern and the floating of nonmetallic inclusions in the mold when pouring steel in top casting. The study of the effect of the speed and direction of metal flows in the mold on the time of floating up of nonmetallic inclusions is very important for the process of finishing alloying and modification of steel in the mold during casting. The purpose of this study was to substantiate the similarity numbers for physical modeling of this process and to determine their influence on the surfacing time as well as determination of the rational casting method for the final alloying steel from the point of view of NMI removal and the mode of additives. In the course of the literature analysis, it was found that the movement of flows during steel casting can be described by the Reynolds, Froude and Weber numbers, but their simultaneous compliance is impossible. Since no substantiation of the insignificant influence of the Weber number, in contrast to the Reynolds number, was found in early studies, the authors developed a technique, assembled an experimental facility and carried out physical modeling. The results of physical modeling confirm the self-similarity of the Weber number in the range from 104.75 to 105.5 . According to the results of this study, the insignificant effect of the Weber number on the process of floating up of nonmetallic inclusions when filling the mold in top casting was confirmed. It was found that the removal of deoxidation products occurs faster in top casting, and the time for their removal is significantly reduced with an increase in the liquid level in the mold at the time of additives.
Keywords: final alloying; self-similarity; Weber number; steel top casting